Significance of finite difference approach for application of Cattaneo-Christov theory conveying radiative ternary-hybrid nanofluids flow - Saira Naz; T. Hayat; Shaher Momani (Heliyon)
This paper investigates the characteristics of ternary-hybrid nanoliquid for time-dependent Darcy-Forchheimer flow. Formulation is based for mixture of water subject to ternary nanoparticles with different shapes like (platelet, spherical and cylindrical). Heat transfer consists of convective condition, radiation and heat generation. Appropriate variables are used to generate dimensionless nonlinear system. Analysis is carried out for Cattaneo-Christov heat flux and variable thermal conductivity. Finite difference method (FDM) is utilized to construct solutions. Salient characteristics of sundry variables are discussed. Analysis is carried out for Nusselt number and skin friction. Present results may have relevance in renewable energy process, polymer extrusion and metallurgy.